Internal variables in macrodynamics of two-dimensional periodic cellular media - Cielecka, I.; Woźniak, C.; Woźniak, M. (Archives of Mechanics, 1998)
A new continuum model for studying the plane strain problems in elastodynamics of a cellular medium having a periodic structure is proposed. The model is based on the concept of macro-internal variables, [17], being capable of describing structures of an arbitrary complex lay-out. The continuum model equations constitute a certain generalization of the plane Cosserat continuum equations coupled with the ordinary differential equations for internal variables. The results are applied to the analysis of free vibration and wave propagation problems. The physical correctness of the model proposed is shown by comparing the obtained solutions to the exact ones.